1985
DOI: 10.1093/bja/57.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Airway Patency in the Unconscious Patient

Abstract: Airway patency was explored in patients breathing spontaneously under deep halothane anaesthesia. Opening and closing of the airway was observed with a flexible bronchoscope looking proximally from the nasopharynx at the epiglottis and the tongue. With the occiput elevated at various angles the smallest angle of retroflexion of the neck necessary to open the airway was measured. The influence of artificial airways on this angle of retroflexion was measured. Cadaveric preparations of the upper airway were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
6

Year Published

1986
1986
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(68 citation statements)
references
References 3 publications
0
62
0
6
Order By: Relevance
“…In the difficult ventilation setting in the Basic Airway Model, effective jaw thrust and head tilt manoeuvres will clear the airway to make mask ventilation possible, which we believe closely resembles real life situations. Boidin found that in anaesthetised patients, the epiglottis was the main cause of airway obstruction and displacing the hyoid anteriorly relieved the obstruction in most cases [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the difficult ventilation setting in the Basic Airway Model, effective jaw thrust and head tilt manoeuvres will clear the airway to make mask ventilation possible, which we believe closely resembles real life situations. Boidin found that in anaesthetised patients, the epiglottis was the main cause of airway obstruction and displacing the hyoid anteriorly relieved the obstruction in most cases [9].…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that placement of a pillow under the patient's head opens the oropharynx. 18 In addition, chin lift, thrusting the jaw forward or extension of the head also widens the oropharyngeal space. 19,20 In our patients, during the manual in-line position, it was often difficult to advance the fibrescope through the space between the epiglottis and posterior pharyngeal wall, and it was possible to insert the fibrescope into the trachea within two minutes in only eight of 20 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sedation causes a decreased airway calibre and airway obstruction; the most consistent site of obstruction is at the nasopharyngeal level where the soft palate becomes approximated to the posterior pharynx. 4 In the event of deterioration in the airway with sedation, it may be necessary to reverse the effects of one or both of the agents rapidly and naloxone and flumazenil should be immediately available. Finally, the method of airway topicalization is usually operator-dependent; the operator should have a mechanism to determine that topicalization is adequate.…”
Section: Complete Airway Obstruction I N This Issue Of the Journal Mmentioning
confidence: 99%
“…La s6dation diminue le calibre des voies a6riennes et cause de l'obstruction ; c'est le nasopharynx qui constitue le plus souvent le site de l'obstruction, A l'endroit o6 le palais mouse rapproche de la paroi post&ieure du pharynx. 4 Si une d&&ioration des voies a6riennes survient lors de la s6dation, il peut ~tre n&essaire de renverser rapidement les effets de l'un des agents, ou des deux, et le naloxone et le flumaz6nil devraient &re imm6diatement disponibles. Enfin, ajoutons que la pulv&isation des voles a&iennes d6pend habituellement de l'op6rateur; ce dernier devrait pouvoir d&erminer l'efficacit6 de la pulv&isation.…”
Section: Obstruction Complande Des Voies a Riennesunclassified